PENGARUH BIAYA AUDIT TERHADAP KUALITAS AUDIT DAN DETERMINAN BIAYA AUDIT - Nunung Nuryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Financial information is one of the important information in decision making. However, many cases of fraud committed by management so that the information in the financial statements cannot be relied upon in decision making. Therefore, the auditor's job is to ensure that the company's financial statements are represented correctly (faithful representation) so that financial statement information becomes more quality and useful in making decisions. So this study aims to examine the effect of audit fee on audit quality. In addition, this study also examines important determinants of audit costs, namely company size, profitability, audit risk, complexity, and firm size. By using the purposive sampling method, samples of the financial and manufacturing industry in 2010-2017 used are 39 firms per year. This sample is used to examine the effect of audit fee on audit quality and the determinant of audit fee using simple linear regression analysis and multiple linear regression analysis. The result of this research shows that audit fees have a significant positive effect on audit quality. In addition, this study shows that firm size, complexity, and firm size are important determinants that determine audit fee. However, profitability and audit risk have not been proven to explain audit fees. Keywords: Audit Quality, Audit Fee, Firm Size, Profitability, Audit Risk, Complexity, Auditor Size Referencens: Al-Harshani, Meshari O. (2008), The pricing of audit services: Evidence from Kuwait. Managerial Auditing Journal, 23(7), 685–696. Al-Thuneibat, Ali. Abedalqader, Ream Tawfiq Ibrahim Al Issa, & Rana Ahmad Ata Baker, (2011), Do audit tenure and firm size contribute to audit quality? Empirical evidence from Jordan. Managerial Auditing Journal, 26(4), 317–334. Arens, Alvin A., Randal J. Elder,. Mark S. Beasley (2014), Auditing and Assurance Services: An Integrated Approach. United States: Pearson Education, Inc. Association of Certified Fraud Examiners (2018), Report to the Nations: 2018 Global Study on Occupational Fraud and Abuse, United States: ACFE. Bhandari, L. C. (1988), Debt/Equity Ratio and Expected Common Stock Returns : Empirical Evidence. The Journal of Finance, 43(2), 507–528. Bowerman, Bruce L., Richard T. O'Connell, Emily S. Murphree (2017), Business Statistics in Practice, Eighth Edition, New York: McGraw Hill Education. Brealey, Richard A., Myers, Stewart C. (2000), Principles of Corporate Finance, Boston: McGraw Hill Companies, Inc. Carey, P. J. (2008), The Benefits of Services Provided by External Accountants to Small and Medium Sized Enterprises. Carey, P., & Simnett, R. (2006), Audit partner tenure and audit quality. Accounting Review, 81(3), 653–676. Castro, Walther Bottaro de Lima, Ivam Ricardo Peleias, & Glauco Peres da Silva (2015), Determinants of Audit Fees: A Study in the Companies Listed on the BM&FBOVESPA, Brasil. Revista Contabilidade & Finanças, 26(69), 261–273. Chen, C. (2008), Audit Partner Tenure , Audit Firm Tenure , and Discretionary Accruals : Does Long Auditor Tenure Impair Earnings Quality ?, 25(2), 415–445. Cooper, D. R., & Schindler, P. S. (2014), Business Research Methods (Twelfth Edition). New York: McGraw-Hill/Irwin. DeAngelo, L. E. (1981), Auditor size and audit quality. Journal of Accounting and Economics, 3(3), 183–199. Dechow, Patricia. M., Richard. G. Sloan, & Amy P. Sweeney (1995), Detecting Earnings Management. The Accounting Review. DeFond, M., & Zhang, J. (2014), A review of archival auditing research. Journal of Accounting and Economics, 58(2–3), 275–326. Deis, Donald R., & Gary Giroux (1996), The effect of auditor changes on audit fees, audit hours, and audit quality. Journal of Accounting and Public Policy, 15(1), 55–76. Eilifsen, Aasmund, Jr William F Messier, Steven M Glover, Douglas F Prawitt (2014), Auditing & Assurance Services, Third Edition, London: McGraw-Hill. Ettredge, Michael., Elizabeth Emeigh Fuerherm, & Chan Li (2014), Fee pressure and audit quality. Accounting, Organizations and Society, 39(4), 247–263. Ferri, Michael G., & Wesley H. Jones (1979), Determinants of financial structure: a new methodological approach. The Journal of Finance, 34(3), 631–643. Francis, Jere. R. (2011), A Framework For Understanding And Researching Audit Quality. Auditing, 30(2), 125–152. Ghozali, H. Imam (2016), Aplikasi Analisis Multivariete dengan Program IBM SPSS 23, Edisi ke-8, Semarang: Badan Penerbit Universitas Diponegoro. Gitman, Lawrence J., Chad J. Zutter (2012), Principles Of Managerial Finance (Thirteenth). United States: Lawrence J. Gitman. Hoitash, Rani., Ariel Markelevich, & Charles A. Barragato (2007), Auditor fees and audit quality. Managerial Auditing Journal, 22(8), 761–786. Horngren, Charles T., L. Sundem, John A. Elliott (1999), Introduction to Financial Accounting, Seventh Edition, New Jersey: Prentice-Hall,Inc. Ikatan Akuntansi Indonesia (2017), Standar Akuntansi Keuangan (SAK), Jakarta: IAI International Accounting Standard Board (2018), The Conceptual Framework for Financial Reporting 2018. London : IASB. Jan, Chyan Long (2018), An effective financial statements fraud detection model for the sustainable development of financial markets: Evidence from Taiwan. Sustainability (Switzerland), 10(2). Jensen, Michael C., & William H. Meckling (1976), Theory Of The Firm : Managerial Behavior , Agency Costs And Ownership Structure, 3, 305–360. Joshi, P. L., & Hasan AL-bastaki (2000), Determinants of Audit Fees : Evidence from the Companies Listed in Bahrain, 138(November 1999), 129–138. Jubb. (1996), Audit fee determinants: The plural nature of risk. Managerial Auditing Journal, 11(3), 25–40. Kieso, Donald E., Jerry J. Weygandt, & Paul D. Kimmel (2013), Financial Accounting IFRS Edition. United States: John Wiley & Sons, Inc. Kieso, Donald E, Jerry J Weygandt, Terry D Warfield (2018), Intermediate Accounting: IFRS Edition Third Edition, United States: John Willey & Sons, Inc. Kikhia, Hassan Yahia (2014), Determinants of Audit Fees: Evidence from Jordan. Accounting and Finance Research, 4(1), 42–53. Knechel, Robert W., & Ann Vanstraelen (2007), The Relationship between Auditor Tenure and Audit Quality Implied by Going Concern Opinions. AUDITING: A Journal of Practice & Theory, 26(May), 113–131. Knechel, W. Robert, Gopal V. Krishnan, Mikhail Pevzner, Lori B Shefchik, & Uma K. Velury (2013), Audit quality: Insights from the academic literature. Auditing, 32(SUPPL.1), 385–421. Konrath, Larry F. (2002), Auditing A Risk Analysis Approach, Fifth Edition, South Western. Kusharyanti (2013), Analysis of the Factors Determining the Audit Fee. Journal of Economics, Business, and Accountancy | Ventura, 16(1), 147–160. Lennox, C. (1999), Are large auditors more accurate than small auditors? Accounting and Business Research, 29(3), 217–227. Lennox, C. S. (1999) Audit quality and auditor size: An evaluation of reputation and deep pockets hypotheses. Journal of Business Finance and Accounting, 26(7–8), 789–805. Liu, Siheng. (2017), An Empirical Study: Auditors’ Characteristics and Audit Fee. Open Journal of Accounting, 06(02), 52–70. Lobo, Gerald, & Yuping Zhao (2013), Relation between Audit Effort and Financial Report Misstatements: Evidence from Quarterly and Annual Restatements. Journal of International Accounting Research, 90(4), 1395–1435. Manry, David L, Theodore J. Mock, & Jerry L. Turner (2008), Does increased audit partner tenure reduce audit quality? Journal of Accounting, Auditing and Finance, 23(4), 553–572. Mohammed, Nishtiman Hashim, & Abdullah Saeed Barwari (2018), Determinants of Audit Fees : Evidence from UK Alternative Investment Market. Academic Journal of Nawroz University, 7(3), 34–47. Musah, A. (2017), Determinants of Audit fees in a Developing Economy: Evidence from Ghana. International Journal of Academic Research in Business and Social Sciences, 7(11). Newton, Nathan J., Dechun Wang, & Michael S. Wilkins (2013), Does a lack of choice lead to lower quality? evidence from auditor competition and client restatements. Auditing, 32(3), 31–67. Nikkinen, J., & Petri Sahlström (2004), Does Agency Theory Provide a General Framework for Audit Pricing ? International Journal of Auditing, 8, 253–262. Ohidoa, T., & Okun, O. O. (2018), Firms Attributes and Audit Fees in Nigeria Quoted Firms. International Journal of Academic Research in Business and Social Sciences, 8(3), 685–699. Pham, Ngoc Kim, Hung Nguyen Duong, Tin Pham Quang, & Nga Ho Thi Thuy (2017), Audit Firm Size, Audit Fee, Audit Reputation and Audit Quality: The Case of Listed Companies in Vietnam. Asian Journal of Finance & Accounting, 9(1), 429. Rahman, Dr Onaolapo Adekunle Abdul, Ajulo Olajide Benjamin, Onifade Hakeem Olayinka (2017), Effect of Audit Fees on Audit Quality: Evidence from Cement Manufacturing Companies in Nigeria. Effect of Audit Fees on Audit Quality: Evidence from Cement Manufacturing Companies in Nigeria., 5(1), 6–17. Rahmina, Listya Yuniastuti, & Sukrisno Agoes (2015), Influence of Auditor Independence, Audit Tenure, and Audit Fee on Audit Quality of Members of Capital Market Accountant Forum in Indonesia. Procedia - Social and Behavioral Sciences, 164(August), 324–331. Republik Indonesia (2008), Undang-Undang Republik Indonesia Nomor 20 tahun 2008 Tentang Usaha Mikro, Kecil, Dan Menengah. Sandra, & Patrick. (1996), The Deteminants of Audit Fees in HongKong: An Empirical Study. Asian Review of Accounting, 4(2), 32–50. Scott, William R (2015), Financial Accounting Theory, Seventh Edition, United States: Pearson Canada Inc. Shibano, T. (1990), Assessing Audit Risk from Errors and Irregularities. Journal of Accounting Research, 28(1990), 110. Sivathaasan, N., R. Tharanika, M. Sinthuja, V. Hanitha (2013), Factors determining Profitability: A Study of Selected Manufacturing Companies listed on Colombo Stock Exchange in Sri Lanka. European Journal of Business and Management, 5(27), 99-107–107. Subramanyam, K. R. (2014), Financial Statement Analysis, Eleventh Edition, New York: McGraw-Hill Education. Sun, Jerry, & Guoping Liu (2011), Client-specific litigation risk and audit quality differentiation. Managerial Auditing Journal, 26(4), 300–316. Tritschler, Jonas (2013), Audit Quality: Association Between Published Reporting Errors and Audit Firm Characteristics. Vu, Dinh Ha Thu Vu (2012), Determinants of audit fees for Swedish listed non-financial firms in NASDAQ OMX Stockholm. Whittington, Ray & Kurt Pany (2004), Principles of Auditing and Other Assurance Services, New York: McGraw-Hill/Irwin. Williams, David D. (1988), The Potential Determinants of Auditor Change. Journal of Business Finance & Accounting, 15(2), 243–261. Wooten, T. C. (2003), Research About Audit Quality. Wu, Shu-Hsing, Tsung-Che Wu, & Kun-Lin Yang (2017), Fair Value Information, Audit fees and Audit Committee in Taiwan. International Journal of Financial Research, 8(2), 124. Xu, Jiabing (2017), Analysis on the Relationship between Audit Fee Management and Audit Quality in China, 53(ICEM 2017), 530–533.